STAFF PERSONNEL ADMINISTRATIVE PRACTICES APPLIED BY SCHOOL’ HEADS FOR ENHANCING TEACHERS JOB COMMITMENT IN PRIMARY SCHOOLS IN VOINJAMA CITY, LOFA COUNTY, REPUBLIC OF LIBERIA - Bosah, Ifeoma Patience; Luogon, Roseline Miaway (Journal of Early Childhood and Primary Education, 2026)
This study examined staff personnel administrative practices applied by school’ heads for enhancing teachers job commitment in primary schools in Voinjama City, Lofa County, Republic of Liberia. Two research questions guided the study while two null hypotheses were formulated and tested at 0.05 level of significance. The study adopted a descriptive survey research design. The population of the study comprised 65 head-teachers and 841 teachers from all the 65 government primary schools in Voinjama City, Lofa County, Liberia. The sample consisted of 65 headteachers and 300 teachers using purposive sampling technique. A validated structured questionnaire titled “Staff Personnel Administrative Practices of Head-teachers (SPAPH) was employed. Cronbach Alpha method was used to determine the internal consistency of the instrument and reliability coefficient of 0.84 and 0.78 respectively was established. The data collected were analyzed using descriptive statistics of mean and standard deviation. The hypotheses were tested using t-test at 0.05 level of significance. It was revealed that both head-teachers and teachers were of the view that head-teachers applied staff professional development practices and motivational practices in. enhancing teachers’ job commitment. It was also revealed that there was no significant difference in the perceptions of head-teachers and teachers in the head-teachers’ application of staff professional development practices. It was recommended amongst others that head-teachers should as a matter of sustainability continue enhancing teachers by furnishing staff offices so as to make them more conducive for work. This is to create a healthy environment for teachers to stay in the school for lesson preparation, marking of pupils’ exercises and other important school works, through this the educational objectives will be achieved.
Keywords: Administration; administrative practices; staff personnel; teachers’ commitment; primary education